Relief for Spain (extract from letter from International Federational of Trade Unions) - International Federation of Trade Unions
032-0148-001 TRADES UNION CONGRESS CORRESPONDENCE. Extract from letter sent to International Department. Name of Sender: International Federation of Trade Unions. Address: 9 avenue d'Orsay, Paris, VIIe. Date: 7th January, 1939. Subject: Relief for Spain. Another matter about which I take this opportunity of drawing your attention is the old trouble we have with regard to relief for Spain. You will remember that I wrote to you in the beginning of December about Gillies' scheme for sending standard parcels for Christmas and the New Year to Spain, and have them distributed by the National Committee for Aid. In spite of my representations that it was impossible for our comrades in Barcelona to collaborate with that body (see my letter of the 9th December), Comrade Gillies went on sending wires to Comrade Santiago asking for the addresses of poor families to whom these standard parcels should be sent by the National Committee. He went on insisting right up to the 26th December! Finally, Comrade Santiago, not knowing what arrangements we had made, gave in and sent him some addresses. I was very angry about this and told Santiago that it would not happen again, but I was very surprised that Comrade Gillies, after my letter of the 9th December, should have gone on with his efforts in a direction absolutely contrary to the policy of the International Solidarity Fund. [SEE OVER FOR CONTINUATION. 292/946/32/148